No talking - Clements, Andrew, 1949-; Elliott, Mark (New York : Simon & Schuster Books for Young Readers, 2007)
The noisy fifth grade boys of Laketon Elementary School challenge the equally loud fifth grade girls to a "no talking" contest
Ages 8-12
A Junior Library Guild selection
Keywords: Behavior -- Juvenile fiction; Contests -- Juvenile fiction; Conduct of life -- Juvenile fiction; Communication -- Juvenile fiction; Schools -- Juvenile fiction